FAKTOR KEPUASAN WPOP ATAS IMPLEMENTASI CORETAX: KEMUDAHAN, KEBERMANFAATAN, DAN KUALITAS SISTEM - Dea Paramitha; I.G.A.N Alit Sumantri; I Gusti Agung Ayu Pramita Indraswari (Universitas Prof.Hazairin,SH Bengkulu, 2026)
This study examines factors influencing the satisfaction of Individual Taxpayers (WPOP) toward the implementation of Coretax in Denpasar. The research focuses on three main variables: perceived ease of use, perceived usefulness, and system quality. We used a quantitative technique based on primary data obtained from surveys given to Coretax WPOP users. Using SPSS, we ran several linear regressions on the collected data. The findings indicate that “perceived ease of use, perceived usefulness, and system quality have positive and significant effects on taxpayer satisfaction, with system quality emerging as the most dominant factor.” These results suggest that improving system stability, usability, and perceived benefits is essential to enhance user satisfaction in digital tax services. The study contributes to the development of technology acceptance research in the context of digital tax administration and provides practical implications for optimizing Coretax implementation.